RACTA 2018 : Ricerche di Archeologia Cristiana, Tardantichità e Altomedioevo = Researches on Christian Archaeology, Late Antiquity and Early Middle Ages : 1st international conference of PhD students, Rome, 5th-7th February 2018 - Cecalupo, Chiara; Lanzetta, Giovanna Assunta; Ralli, Priscilla (Access archaeology., 2019)
RACTA (Ricerche di Archeologia Cristiana, Tardantichità e Altomedioevo) was the first international conference for PhD students of Christian archaeology. It took place in Rome in February 2018, hosted by Pontificio Istituto di Archeologia Cristiana and gathered more than 50 multidisciplinary talks and posters from PhD students from Europe, America and Russia. The engagement shown at the well-attended event, and the interest of several institutions, proved that Christian archaeology continues to be important to new generations of archaeologists, art historians, and researchers of the ancient world.